The Impact of Self-Transcendence on Anxiety Among Chinese College Students: The Moderating Roles of Self-Enhancement and Dominant Self-Construal - Hong Wang; Tong Yue; Huajun Luo (Behavioral Sciences)
This study explores the role of self-transcendence values in reducing anxiety among Chinese undergraduates, with a particular focus on how self-enhancement values and self-construal styles moderate this relationship. A total of 567 undergraduate students were assessed using the Portrait Values Questionnaire (PVQ-21), the Trait Anxiety Inventory (T-AI), and the Self-Construal Scale (SCS). Hierarchical regression and moderated moderation analyses were conducted to test the interactions between the variables. The findings suggest that self-enhancement moderated the association between self-transcendence and anxiety, particularly in individuals with low self-enhancement. Furthermore, the moderating effect of self-enhancement was influenced by dominant self-construal. These findings have practical implications for integrating value-based interventions in educational and public health strategies aimed at improving mental well-being among university students.